Factors favorables to the development of the investigative culture of university teachers - Criado Dávila, Yvette Vanessa (2020)
The university has several functions, such as teaching, responsibility and research. In relation to research, it is considered as an activity carried out by teachers and as an activity it has elements: agents, organization and results. In addition, it has areas such as the research process and the research culture. This research culture manifests as beliefs, values and attitudes and has factors that influence it. Among the factors are the presence of clear objectives and leadership of university management, the training and support provided to teachers as part of their professional preparation, the existence of research centers, the recognition of research at teachers, the promotion of collaboration; as well as the investment of time and financing. This synergy of factors favors the development of the research culture in the university.